BATIK DAN KERIS SEBAGAI DASAR PENGEMBANGAN MUATAN LOKAL PENDIDIKAN BERKARAKTER PADA ANAK USIA DINI (PAUD) DI YAYASAN UWAIS-AL QORNI SURAKARTA - Kuntadi Wasi Darmojo; basuki Teguh Yuwono; Sri Marwati (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
Education and training of PPM, Education Foundation Uwais Al Qorni KB and TK Natural Integrated Uwais Al Qorni Surakarta has a goal to introduce and at the same time able to provide knowledge and skills base level of batik and keris to the kindergarten teachers, to be developed into a model character education in early childhood education (ECD). The method used to achieve the targets achieved in the implementation of the training are: (1). Participatory approach, (2). Personal approach, and (3). The principle of partnership. Then another strategy is the participation of institutions Education Foundation Uwais Al Qorni Surakarta is selecting and motivating participants to be able to attend training from start to finish in order to understand and applying all of the material that is taught to early childhood education. Target reached is the teachers know batik and keris and may apply to early childhood education as the basis of local content in character. So the follow-up to this training, is their character education model of learning in early childhood, which can be passed and applied in other schools through the Association of Teachers Radiatul Anfal Surakarta.